Formulasi dan Uji Mutu Fisik Sediaan Sheet Mask dari Sari Buah Lemon Cui (Citrus microcarpha Bunge) Sebagai Antiaging - Salsabila Nada; Arfiani Arifin; Razifah Suci Mawarni; Abdul Vashar Adi (Program Studi Farmasi, Universitas Islam Makassar, 2024)
Cui lemon (Citrus microcarpa Bunge), also known as fish lemon or calamansi lemon, contains vitamin C, citric acid and flavonoids which have antiaging potential. This research was conducted to formulate Lemon Cui fruit juice in a sheet mask preparation that meets the physical quality test requirements. The method of this research is that a sample of Lemon Cui juice is obtained by grinding it using a blender by adding enough water and then separating the pulp until the juice is obtained. The sheet mask formulation used varying concentrations of Cui lemon juice lyophilisate samples, namely F1 (0.5%), F2 (1%), F3 (1.5%), and negative control (without lyophilisate). Physical quality testing includes organoleptic tests, homogeneity tests, pH tests and irritation tests. The results obtained were physical quality testing of F1 (0.5%), F2 (1%), F3 (1.5%), and negative control (without lyophilisate) fulfilling the physical quality test requirements, including organoleptic tests, homogeneity, pH, and irritation test.